Human rights and humanitarian norms, strategic framing, and intervention : lessons for the responsibility to protect - Labonte, Melissa (Global institutions series, 2012)
The human rights and humanitarian landscape of the modern era has been littered with acts that have shocked the moral conscience of mankind, and there has been wide variation in whether, how, and to what degree states respond to mass atrocity crimes, even when they share similar characteristics. In many cases concerned states responded, either through moral suasion; gentle or coercive diplomacy; or other non-forcible measures, to prevent or halt the indiscriminate human rights violations that were occurring. In others, states simply turned away and left the vulnerable to their fate. And sti.